The Implementation of Benjamin Graham Criteria (A Case in Indonesia Market) - Rachmattulah, Mohammad Fahmi; Faturrohman, Taufik (Journal of Business and Management, 2016)
Abstract. Utilizing data of publicly listed companies on the Indonesian Stock Exchange for the period spanning from 2006 to 2015, the present study examines the profitability of stock selection criteria of Benjamin Graham in the Indonesian capital market. The different risk-reward combinations of the 10 Benjamin Graham Criteria and the minimum number of criteria to be fulfilled by a stock in order to provide excess returns to the investor are examined using independent sample T-test, Sharpe ratio, Treynor ratio and the capital asset pricing model (CAPM). The results show ample evidence that almost all of the risk-reward combinations proposed by Benjamin Graham can be used by investors in order to obtain excess returns except for the combination of discount to net current asset value (NCAV) and consistent past earnings growth. Furthermore, stocks which meet at least two Graham criteria can yield excess returns to investors if such stocks are held for the period of 24 months. Additionally the more Graham criteria which a stock fulfill, the more likely that the stock will generate positive excess return to the investor.Keywords: Benjamin Graham, value investing